Late Pleistocene glaciolacustrine MIS 3 record at Fagnano Lake, Central Tierra del Fuego, southern Argentina. (July 2021) - Sanci, Romina; Orgeira, María J.; Coronato, Andrea; Tófalo, Rita; Panarello, Héctor O.; Quiroga, Diego; López, Ramiro; Palermo, Pedro; Gogorza, Claudia S.
Abstract: A late Pleistocene glaciolacustrine record was studied at Fagnano Lake (54°35´S, 67°20´W), central Isla Grande de Tierra del Fuego, southernmost South America. Two profiles from the Río Valdéz outcrop were collected for isotopic, geochemical, sedimentological, and geophysical analyses. The sedimentological characteristics, such as rhythmites, presence of dropstones, absence of fossil record, and scarce presence of organic matter, suggest deposition in an ice-contact lake, possibly dammed by the Fagnano paleoglacier. Organic matter of C3 plant origin suggests certain cold and wet conditions. A chronology of the late Pleistocene outcrop was obtained from five 14 C ages resulting in an age-depth model. The time span covered 49.01 cal ka BP to 32.14 cal ka BP. Based on the thickness of the deposit and the calculated average sedimentation rate, the glacial environment could have been present in the study area prior to the last glacial maximum, in agreement with the Inútil-San Sebastián paleoglacier. Both glaciers flowed from the same mountain ice sheet in the Darwin Cordillera, which makes it possible to infer a different behavior of this ice cap from those of the Patagonian Andes, perhaps forced by different atmospheric dynamics and proximity to the wet and cold subantarctic air masses.